2014
DOI: 10.1037/hea0000057
|View full text |Cite
|
Sign up to set email alerts
|

Negative social interactions and incident hypertension among older adults.

Abstract: Objective To determine if negative social interactions are prospectively associated with hypertension among older adults. Methods This is a secondary analysis of data from the 2006 and 2010 waves of the Health and Retirement Study, a survey of community-dwelling older adults (age >50). Total average negative social interactions were assessed at baseline by averaging the frequency of negative interactions across four domains (partner, children, other family, friends). Blood pressure was measured at both waves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 118 publications
1
42
0
2
Order By: Relevance
“…This study adds to the growing evidence that the effects of close relationship experiences on later mental and physical health may differ for men and women (e.g., Gustafsson et al, 2012; Shih et al, 2006; Sneed & Cohen, 2014; Vaughan, Foshee, & Ennett, 2010). We found evidence that both parent-adolescent relationships and friendship closeness with boys were predictors of metabolic risk for female but not male participants.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This study adds to the growing evidence that the effects of close relationship experiences on later mental and physical health may differ for men and women (e.g., Gustafsson et al, 2012; Shih et al, 2006; Sneed & Cohen, 2014; Vaughan, Foshee, & Ennett, 2010). We found evidence that both parent-adolescent relationships and friendship closeness with boys were predictors of metabolic risk for female but not male participants.…”
Section: Discussionmentioning
confidence: 76%
“…Further, some evidence suggests that women have stronger physiological responses to negative social experiences (e.g., Kiecolt-Glaser & Newton, 2001; Stroud, Salovey, & Epel, 2002). Recently, in a sample of older adults, Sneed and Cohen (2014) found that negative social interactions were associated with increased odds of developing hypertension across a four-year period for women but not for men. It may be that social experiences with parents and friends in adolescence are more likely to predict metabolic outcomes for women than men.…”
mentioning
confidence: 99%
“…This holistic model also brings into question the possible negative effects of the downstream factors that may link networks to undesirable health outcomes (Sneed and Cohen, 2014).…”
Section: Theories Of the Impact Of Social Engagement On Healthy Agingmentioning
confidence: 99%
“…These studies typically include controls for sociodemographic characteristics, health conditions, biological risk factors, and health behaviors. Some studies also control for depressive symptoms and traits such as neuroticism or hostility (e.g., DeVogli et al, 2007; Sneed & Cohen, 2014), making it unlikely that the effects of negative exchanges are an artifact of participants’ mental health or personality characteristics.…”
Section: Evidence Linking Positive and Negative Social Exchanges To Hmentioning
confidence: 99%